PENGARUH DOSIS BIOHERBISIDA FORMULASIUNIHAZ DALAM PENGENDALIAN GULMA RUMPUT BELULANG( Eleusine indica L.) - Pranata, Gusti; Anwar, Risvan; Suzanna, Eka; Djatmiko, Djatmiko (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
This study aims to determine the effect of doses of bioherbicide formulated by Unihaz in controlling weeds, as well as to determine the dose of bioherbicide formulated by Unihaz which is effective in controlling weeds. This study used a single factor Completely Randomized Design (CRD), namely the Unihaz formulation bioherbicide dose treatment, consisting of 7 levels with 4 replications. The treatments were: dose 1 (40 l/ha), dose 45 l/ha, dose 50 l/ha, dose 55 l/ha, dose 60 l/ha, dose 60 l/ha, and dose 70 l/ha. The data obtained were then analyzed using Fisher's test (F), followed by Duncan's Multiple Range Test (DMRT) with a test level of 5%. The results of this study concluded that the use of a dose of 70 l/ha showed the highest weed mortality rate and the lowest live weed population, the lowest weed wet weight and dry weight which were significantly different from other dose treatments, making it the most effective in controlling grassy grass weeds